Drivers of Adoption: How Innovation Attributes Influence the Diffusion of Digital Tools in Indonesia’s Merdeka Curriculum - Maharani, Siti Dewi; Pramudya, Arya; Amira, Sashi (International Journal of Education and Learning Studies, 2025)
This study investigates the influence of innovation attributes on the diffusion of educational technology within Indonesia’s Merdeka Curriculum using an explanatory sequential mixed-methods design. Quantitative analysis of 120 elementary teachers revealed that relative advantage and compatibility significantly promote technology adoption, while complexity hinders it. Qualitative findings from a subset of participants elucidate these results, identifying three key contextual drivers that shape the salience of these attributes: (1) institutional and peer support, which enhances perceived ease of use and trialability; (2) pedagogical relevance, which critically underpins perceptions of relative advantage and compatibility; and (3) socio-cultural adaptation, which emerged as a core component of perceived compatibility in this context. Teachers adopt digital tools such as Canva and augmented reality more readily when these tools are embedded within supportive structures and aligned with local pedagogical and cultural contexts. The study extends Rogers’ Diffusion of Innovations theory by theorizing socio-cultural adaptation and institutional readiness not merely as external conditions, but as integral factors that dynamically shape educators' perceptions of core innovation attributes. Findings suggest that meaningful adoption requires not only access to technology but also continuous training, supportive school leadership, and culturally responsive practices to ensure sustainable innovation in primary education.